Smoking & stroke: best practices for your patients - Pipe, Andrew (Henry Stewart Talks, 2018)
Smoking cessation in clinical practice, Preconceptions about smoking, Tobacco addiction & stroke statistics in smokers, Second-hand smoke, Smoking effect blood pressure control and statin use, The cigarette as a drug delivery device, Nicotine levels in blood, Nicotine effect on the CNS, Caffeine intake altered by cessation, Nicotine replacement therapy (NRT) and its use in CVD patients, Bupropion compared to NRT, New medications and approaches, Ottawa model for smoking cessation